2012
DOI: 10.1177/1088357612459270
|View full text |Cite
|
Sign up to set email alerts
|

Procedural and Conceptual Print-Related Achievements in Young Children With Autism Spectrum Disorders

Abstract: A comparative analysis between emergent procedural and conceptual print-related achievements was conducted for 32 children with autism spectrum disorders (ASD) aged 4 to 8 years. To minimize the influence of linguistic competence on the assessment, the ASD print-related profile was compared with that of a language-matched sample of typically developing peers. Two factors associated with young children's print-related achievements, their print motivation and home-based experiences, were illustrated for the matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
1
23
1
2
Order By: Relevance
“…Previous research has indicated that young children with ASD do enjoy shared reading, albeit less than TD children (Dynia et al, ; Lanter, Freeman, & Dove, ). However, the influence of language and literacy competence was not taken into consideration, even though these factors are positively associated with attitude to reading for nonautistic children (Chall & Jacobs, ; Frijeters et al, ; Kaderavek & Sulzby, ; Sawyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research has indicated that young children with ASD do enjoy shared reading, albeit less than TD children (Dynia et al, ; Lanter, Freeman, & Dove, ). However, the influence of language and literacy competence was not taken into consideration, even though these factors are positively associated with attitude to reading for nonautistic children (Chall & Jacobs, ; Frijeters et al, ; Kaderavek & Sulzby, ; Sawyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the limited research on the HLE of children with ASD has focused on the preschool years and indicates that the majority of parents read to their child at least twice a week, which is similar to TD families (Dynia et al, ; Lanter, Freeman, & Dove, ). Likewise, the current study of school‐aged children found that 85% of children with ALD participated in shared reading activities on at least a weekly basis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pesquisas indicam que essa população apresenta resultados satisfatórios em tarefas de pré-leitura (reconhecimento de letras do alfabeto), mas insatisfatórios na compreensão de mensagens escritas (KLUTH; CHANDLER-OLCOTT, 2008;LANTER;FREEMAN;DOVE, 2012;). De maneira semelhante, mostram-se, muitas vezes, incapazes de fazer inferências sobre o comportamento de personagens em livros (WHALON et al, 2013).…”
Section: A Leitura Em Educandos Com Autismounclassified